Rekonfigurasi Etika Administrasi sebagai Determinan Mutu Pelayanan Aparatur Sipil Negara dalam Mewujudkan Prinsip Good governance di Kota Palangka Raya - Aprilya Fransisca Natasya; Ica Sridewi; Tiara Tiara (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study provides an in-depth examination of the relationship between the implementation of administrative ethics and the quality of civil service performance within the framework of good governance principles in Kota Palangka Raya. Employing a qualitative–descriptive approach grounded in literature-based analysis, this research explores various empirical findings related to public service practices, bureaucratic transparency, regional asset management, and the integrity of civil servants. The analysis reveals that administrative ethics have not been fully internalized, as evidenced by persistent delays in service delivery, employee absenteeism, convoluted procedures, low responsiveness, and weak accountability and regulatory compliance. These conditions indicate a substantial gap between ideal ethical standards and actual administrative practices. The findings further confirm that core values of administrative ethics—such as integrity, discipline, responsibility, transparency, and professionalism—play a determinant role in realizing good governance principles, including transparency, effectiveness, efficiency, accountability, and the rule of law. This study asserts that strengthening administrative ethics is a strategic prerequisite for improving civil service quality and restoring public trust. The implications highlight the need for continuous capacity-building, enhanced integrity among civil servants, and strengthened oversight mechanisms to establish an equitable, accountable, and citizen-oriented system of governance.